Penerapan Metode Outdoor Activity untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Tema 3, sub-Tema 2: Kebergaman Makhluk Hidup di Lingkunganku - Cacik, Sri; Pratama, Ferry Yudha; Mizan, Saeful (JPB - Jurnal Pendidikan Biologi, 2022)
This study aims to improve the motivation and learning outcomes of 4th grader at MI Miftahul Ulum Pekuwon, Rengel, Tuban after the Outdoor Activity method was applied in Theme 3, sub-Theme 2: The Diversity of Living Things in My Environment. This research is a Classroom Action Research (CAR) conducted in 2 cycles, including planning, implementation, observation and evaluation, and reflection. The research subjects were students of class IV MI Miftahul Ulum, totaling 23 students. Data collection techniques used interviews, observations, tests, and documentation. The data obtained were analyzed by quantitative descriptive methods, including data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, it is known that the average pre-cycle learning outcome is 44.78, with classical completeness 8.7%. In cycle 1, the average percentage of student responses was 90.87% in the very good category and the average learning outcome was 69.13 with 65.22% classical completeness. In cycle 2, the average percentage of student responses was 94.89% in the very good category and the average learning outcome was 78.26 with 95.65% learning completeness. The results of this study indicate that the application of the Outdoor Activity method can increase the motivation and learning outcomes of fourth grade students of MI Miftahul Ulum.